Periodized Aerobic Training Between Thresholds Improves Submaximal Cardiorespiratory Parameters in Octogenarians - Cofre-Bolados, C; Orihuela-Diaz, P (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Background and Aims: The worldwide aging population is expanding, with more individuals living into their 80s. Physiological functions decline gradually with age, compounded by sedentary lifestyles. Incorporating physical activity into daily routine is crucial for maintaining independence. This study aimed to assess a periodized high-intensity aerobic training program (PEZO-BT) in octogenarians, focusing on submaximal ergospirometry effects. Methods: A total of 48 non-frail octogenarian subjects (12 females, 36 males) were randomized into control and intervention groups. All subjects underwent submaximal cardiopulmonary exercise testing with gas analysis at baseline, stopping after the respiratory compensation point (RCP). Our intervention group completed a 14-week PEZO-BT aerobic training program. The outcomes were oxygen consumption at first ventilatory threshold (VO2AT), ventilatory efficiency slope (VE/VCO2), oxygen uptake efficiency slope (OUES), cardiorespiratory optimal point (COP), oxygen pulse change (ΔVO2/HR) from anaerobic threshold (AT) to respiratory compensation point (RCP), and power output at anaerobic threshold (POAT). Results: Mixed ANOVA examined time and treatment effects. If significance emerged, post hoc t-tests were used to compare significances between groups. The homogeneity of variance was assessed using Levene’s test. Chi-square tests compared ergospirometry criteria and ventilatory performance within groups. The mean differences at post intervention were significant in VO2AT (p < 0.001), VE/VCO2 (p < 0.001), ΔVO2/HR (p < 0.05), and POAT (p < 0.001), while OUES and COP were not significant (p > 0.05). However, clinical effects were observed in the entire intervention group. Conclusions: Training improved exercise capacity and workload. Overall, this periodic aerobic and high-intensity interval training (HIIT) program yielded significant improvements in cardiorespiratory fitness (CRF) in previously untrained octogenarians with and without comorbidities. The findings suggest implications for promoting long-term healthy aging. © 2023 by the authors.